Russia’s Economic Position in the Post-Soviet Union Space: the Evolution Between 2000-2019 - TĂTAR, Andrei Viorel (2024)
The main motivation of this thesis is comprised in the change of paradigm, from geopoliticsto geoeconomics enforcing the “soft power” terminology. Alongside the ideological motivation isthe re-emergence of Russian Federation on the international stage. This re-emergence is scarcelyanalyzed and presented in literature, and even more, it is rarely linked to geo-economic factors. Thisprocess developed in time, and the academic analysis failed to cover this subject because of otherurgent issues like the economic crisis, migrant crisis and the wars in the Middle East. It isinteresting how the “Russian bear” has awakened after the Ukrainian Conflict and Russia combinesmilitary (“hard power”) with economics (“soft power”). This things mostly happened because of theRussian need of counterbalancing the economic power of the western bloc, here in name ofEuropean Union and its close partners.